Modified Mesoporous Carbon Material (Pb-N-CMK-3) Obtained by a Hard-Templating Route, Dicyandiamide Impregnation and Electrochemical Lead Particles Deposition as an Electrode Material for the U(VI) Ultratrace Determination - Katarzyna Tyszczuk-Rotko (MDPI AG, 2021)
In this paper, a dicyandiamide-impregnated mesoporous carbon (N-CMK-3), electrochemically modified in situ with lead film (Pb-N-CMK-3), was tested as an electrode material for U(VI) ultratrace determination. The prepared carbon material was characterized by XRD, SEM-EDX, Raman, FT-IR, XPS analysis and nitrogen sorption measurements. The changes of electrochemical properties of glassy carbon electrodes (GCE) after the N-CMK-3 and Pb-N-CMK-3 modification were studied using CV and EIS methods. The modification of the GCE surface by the N-CMK-3 material and Pb film increases the electroactive area of the electrode and decreases the charge transfer residence and is likely responsible for the electrochemical improvement of the U(VI) analytical signal. Using square-wave adsorptive stripping voltammetry (SWAdSV), two linear calibration ranges extending from 0.05 to 1.0 nM and from 1.0 to 10.0 nM were observed, coupled with the detection and quantification limits of 0.014 and 0.047 nM, respectively. The Pb-N-CMK-3/GCE was successfully applied for U(VI) determination in reference materials (estuarine water SLEW-3 and trace elements in natural water SRM 1640a).